Desarrollo de un sistema de control como soporte a la toma de decisiones de datos para laboratoríos clínicos basado en web service - Arteaga Mera, Maria Luisa (2011)
The area of Clinical laboratory, offers to the community a wide range of exams with the purpose of contributing with an opportune and reliable diagnosis for the preservation of the health and the prevention of illnesses. Each exam of clinical laboratory should be carried out the patients in an individual way, being always guided by the professional and ethical parameters. In each one of these topics, it is required of numerous measures of attention and care, with the purpose of minimizing to the maximum the feasible errors of being made in the daily practice. It should be emphasized that the work in the clinical laboratory, as any work type, it is carried out by human beings and it is not exempt of making mistakes. The alternative proposal allows to automate the flow of information in the Clinical Laboratory, including the patient's inscription, generation of the work lists, introduction, prosecution and emission of the results, what impacts in a better organization of the internal activity of the laboratory and it rebounds in a better service to the final users .The statistical data provides the system help to the address of the institution in the taking of decisions, as well as to the medical personnel in the prevention, diagnostic and treatment of illnesses.